Simulation Research on Cutterhead Hydraulic Drive System of Shield Machine. Issue 5 (January 2021) - Wang, Changlin; Chen, Jiwen; Wang, Rijun; Meng, Decai
Abstract: The core of the cutter head drive system of shield machine is the hydraulic system. Combined with a certain type of shield machine, the structure and working principle of 1.8 m hydraulic driving system for cutterhead of shield machine are studied, and the closed loop control mode of variable pump variable motor is adopted to design the 1.8 m hydraulic driving system for cutterhead of shield machine, the simulation model of the cutter head drive system is established in the hydraulic simulation environment, and the parameters of the sub-model are designed according to the actual situation.